Design of a new type of intrinsic safety pilot circuit of magnetic starter - TONG Jun; YIN Hongyu; ZHANG Chengmin; QIU Wendong (Gong-kuang zidonghua, 2014)
In view of shortcoming that intrinsic safety pilot circuit controlled by relay exists unstable faults of self-starting and low-voltage starting, a new type of intrinsic safety pilot circuit with optical coupling isolation of mine-used magnetic starter based on microcomputer control was designed, working principle of the circuit was introduced in details. The practical application shows that the pilot circuit has reliable performance and stable operation.